Comparison of safety profiles of DPP-4 inhibitors with SGLT-2 inhibitors in type 2 diabetes mellitus: a systematic review - Nimavat, Zeel R.; Patel, Ankit N.; Gor, Alpa P.; Ganguly, Barna (International Journal of Basic & Clinical Pharmacology, 2025)
In type 2 diabetes mellitus (T2DM), add-on therapy to metformin is often required. Both sodium-glucose cotransporter-2 (SGLT2) inhibitors and dipeptidyl peptidase-4 (DPP-4) inhibitors are widely used, but differ in their safety profiles due to distinct mechanisms of action. This study aimed to systematically review and compare the safety outcomes of SGLT2 versus DPP-4 inhibitors in patients receiving background metformin therapy. A systematic literature search was conducted in PubMed for studies published from 2006 onward. Randomized controlled trials and observational studies evaluating safety outcomes of SGLT2 inhibitors (empagliflozin, dapagliflozin, canagliflozin) and DPP-4 inhibitors (sitagliptin, teneligliptin, vildagliptin) as add-on to metformin were included. Data on adverse events (AEs), serious adverse events (SAEs), and drug-related adverse events (DRAEs) were extracted and analyzed. Twenty studies met the inclusion criteria: 8 studies on SGLT2 inhibitors (n=946) and 12 on DPP-4 inhibitors (n=1903). The overall incidence of AEs was higher with DPP-4 inhibitors (66%) compared to SGLT2 inhibitors (34%), while DRAEs were comparable (12% vs. 11%). SGLT2 inhibitors were more often associated with genital and urinary tract infections, whereas DPP-4 inhibitors had higher rates of gastrointestinal disturbances and hypoglycemia. Rare events included dehydration and atrial flutter (SGLT2) and dyspepsia and hypertension (DPP-4). Notably, adverse events varied across individual agents within each class. Both SGLT2 and DPP-4 inhibitors demonstrate acceptable safety as add-on therapy to metformin. Given drug-specific adverse events, individualized therapy based on patient characteristics is essential. Further large-scale safety-focused studies are warranted.